(untitled) (Singapore, 1985)
This collection comprises surveys on current algebra and anomalies. Current algebra is virtually a closed subject. Nevertheless it remains our most succesful analysis of fundamental particle interacions.
Keywords: Algebra of currents,Đại số dòng